A role of the claustrum in auditory scene analysis by reflecting sensory change - Remedios, Ryan; Logothetis, Nikos K.; Kayser, Christoph (Frontiers in Systems Neuroscience, 2014)
The biological function of the claustrum remains speculative, despite many years of research. On the basis of its widespread connections it is often hypothesized that claustrum may have an integrative function mainly reflecting objects rather than the details of sensory stimuli. Given the absence of a clear demonstration of any sensory integration in claustral neurons, however, we propose an alternative, data-driven, hypothesis: namely that the claustrum detects the occurrence of novel or salient sensory events. The detection of new events is critical for behavior and survival, as suddenly appearing objects may require rapid and coordinated reactions. Sounds are of particular relevance in this regard, and our conclusions are based on the analysis of neurons in the auditory zone of the primate claustrum. Specifically, we studied the responses to natural sounds, their preference to various sound categories, and to changes in the auditory scene. In a test for sound-category preference claustral neurons responded to but displayed a clear lack of selectivity between monkey vocalizations, other animal vocalizations or environmental sounds. Claustral neurons were however able to detect target sounds embedded in a noisy background and their responses scaled with target signal to noise ratio. The single trial responses of individual neurons suggest that these neurons detected and reflected the occurrence of a change in the auditory scene. Given its widespread connectivity with sensory, motor and limbic structures the claustrum could play the essential role of identifying the occurrence of important sensory changes and notifying other brain areas - hence contributing to sensory awareness.